Breast cancer application protocol: a randomised controlled trial to evaluate a self-management app for breast cancer survivors - Yingchun Zeng; Xiangyu Liu; Andy S K Cheng; Peter H F Ng; Cindy T T Kwok; Michael Feuerstein (BMJ Open)
Introduction The eHealth technologies that are being designed for chronic disease constitute a global trend towards health assessment and self-management. However, most of these approaches tend to focus on a single symptom or problem rather than on the multiple problems that are characteristic of many of these chronic illnesses. The aim of this study is to examine the effectiveness of and adherence to a self-management application (app) that identifies multiple problem areas related to surviving breast cancer as the targeted chronic illness.Methods and analysis This is a randomised controlled study. Eligible participants will be allocated randomly into either an intervention group or a control group at a 1:1 ratio. The intervention group will be assigned to the self-management app (‘Be-with-You’), while the control group will use a general health app (‘Sham’ app). The primary outcomes will include the differences between the two groups in their health literacy, problem-solving skills and self-management skills. The secondary outcomes will include group differences in self-efficacy, readiness for change and health-related quality of life. All of these outcomes will be measured at baseline and at 4 weeks and 12 weeks after intervention. In addition, usability of these two mobile apps will be measured at 4 weeks and 12 weeks after intervention. The planned sample size is 476.Ethics and dissemination The Human Subjects Ethics Sub-committee of The Hong Kong Polytechnic University approved the study (HSEARS20190922001, 24 September 2019). Dissemination of findings will occur at the local, national and international levels.Trial registration number ChiCTR1900026244.